Hydrodynamic Performance of Autonomous Underwater Gliders with Active Twin Undulatory Wings of Different Aspect Ratios - Yongcheng Li; Jianxin Hu; Qiuzhuo Zhao; Ziying Pan; Zheng Ma (Journal of Marine Science and Engineering, 2020)
The propulsive performance of a bio-inspired autonomous underwater glider (AUG) with active twin undulatory wings undergoing undulatory motion was investigated by numerically solving the viscous incompressible Navier–Stokes equations, coupled with the immersed boundary method. The aspect ratio (AR) effects of the undulatory wings were studied. The simulation results showed that with the increase of AR, the thrust force generated by the active twin undulatory wings showed a linear growth, while the propulsion efficiency of the AUG increased to the peak and then decreased. The optimum magnitude of AR around 2 was obtained in the current study. The vortex structures in the wake of the active twin wings are also presented and discussed. The conclusions acquired here could provide guidance for the new conceptual design of bio-inspired AUGs.